2018
DOI: 10.1021/acs.jpca.8b05153
|View full text |Cite
|
Sign up to set email alerts
|

Structure Based Modulation of Electron Dynamics in meso-(4-Pyridyl)-BODIPYs: A Computational and Synthetic Approach

Abstract: The effects of structural modification on the electronic structure and electron dynamics of cationic meso-(4-pyridyl)-BODIPYs were investigated. A library of 2,6-difunctionalized meso-(4-pyridyl)-BODIPYs bearing various electron-withdrawing substituents was designed, and DFT calculations were used to model the redox properties, while TDDFT was used to determine the effects of functionalization on the excited states. Structural modification was able to restructure the low-lying molecular orbitals to effectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 69 publications
(117 reference statements)
5
13
0
Order By: Relevance
“…When compared to the regular BODIPYs and aza-BODIPYs, the DFT-predicted frontier π-orbitals of compounds [5a–c] – , 5a–c , and 8a–c were found to be flipped. Indeed, in the case of the regular BODIPYs and aza-BODIPYs, the HOMO resembles “half” of the classic porphyrin a 1u orbital with a large contribution from the pyrrolic α- and β-carbon atoms, while the LUMO resembles a “half” of the classic porphyrin a 2 u orbital that is dominated by the contribution from the pyrrolic nitrogen atoms and the meso -carbon or nitrogen atom. In the case of MB-DIPYs [5a–c] – , 5a–c , and 8a–c , DFT predicts that the highest energy π-centered orbital has a large contribution from the nitrogen atoms complemented by the significant contribution from the carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…When compared to the regular BODIPYs and aza-BODIPYs, the DFT-predicted frontier π-orbitals of compounds [5a–c] – , 5a–c , and 8a–c were found to be flipped. Indeed, in the case of the regular BODIPYs and aza-BODIPYs, the HOMO resembles “half” of the classic porphyrin a 1u orbital with a large contribution from the pyrrolic α- and β-carbon atoms, while the LUMO resembles a “half” of the classic porphyrin a 2 u orbital that is dominated by the contribution from the pyrrolic nitrogen atoms and the meso -carbon or nitrogen atom. In the case of MB-DIPYs [5a–c] – , 5a–c , and 8a–c , DFT predicts that the highest energy π-centered orbital has a large contribution from the nitrogen atoms complemented by the significant contribution from the carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…While restoration of the meso -(4-pyridyl)-BODIPY fluorescence can be achieved by either inhibiting d-PeT or the ISC, the charge recombination emission can be enhanced to varying degrees by increasing the electrostatic charge of the ‘hole’ created by the electronic excitation and subsequent d-PeT process. We recently showed [ 33 ] that this can be accomplished through the installation of electron-withdrawing groups at the 2,6-positions. As an example, chlorination at the 2,6-positions induced an increase in the fluorescence quantum yield of a meso -4-pyridinium BODIPY from 0.019 to 0.048 in acetonitrile and from 0.004 to 0.038 in water [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed [ 33 ] that this can be accomplished through the installation of electron-withdrawing groups at the 2,6-positions. As an example, chlorination at the 2,6-positions induced an increase in the fluorescence quantum yield of a meso -4-pyridinium BODIPY from 0.019 to 0.048 in acetonitrile and from 0.004 to 0.038 in water [ 33 ]. Furthermore, Ueno and coworkers [ 34 ] reported that the installation of acetyl groups at the 2,6-positions of a meso -(nitroanisole)-BODIPY increased the fluorescence quantum yield of the dye in acetonitrile by over 20-fold (see Figure 2 b).…”
Section: Introductionmentioning
confidence: 99%
“…The 4-pyridyl derivative 4 showed the highest inflection point, possibly because the pyridine N atom in 4 is farther from the sterically hindered 1,7-phenyl groups; therefore 4 could be protonated more easily. Although it has been documented that the fluorescence intensity can be modified by protonation of dyes, few examples of wavelength shifts of the fluorescence have been reported . The observation of such shifts is expected to be fundamentally important because it may help us understand how to control fluorescence shifts, which will allow us to design and construct ratiometric fluorescent probes from smaller molecules.…”
Section: Resultsmentioning
confidence: 98%